ERROR TYPES IN SUBJECT-VERB AGREEMENT - Rifiyanti, Hafizah; Dewi, Dyah Utami (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2022)
The aim of this study is to identify the types of errors in subject-verb agreement. The basic mistakes made by students in subject-verb agreements are a lack of knowledge about sentence patterns and their types. The study applied a qualitative descriptive method. The study is to describe and classify the errors made by the students and identify which parts of the subject-verb agreement have the most errors. The data collection technique of this study is by collecting the results of a worksheet assessment on subject-verb agreement given to 89 students. The data is analyzed by investigating what types of errors the students make and what factors often occur in subject-verb agreement. The results of this indicate that there are errors made by students including: singular subject must agree with a singular verb as well as a plural subject must agree with a plural verb, errors in a compound subject, errors in using the verb of the form have, and errors in be verb. The study implies that grammar and sentence construction, particularly subject-verb agreements, are basic chapters that must be trained continuously and become an important fundamental goal before students learn other things in English.